2021
DOI: 10.1177/01945998211029831
|View full text |Cite
|
Sign up to set email alerts
|

Normative Ambulatory Reflux Monitoring Metrics for Laryngopharyngeal Reflux: A Systematic Review of 720 Healthy Individuals

Abstract: Objectives To review the normative data for acid, weakly acid, and nonacid proximal esophageal (PRE) and hypopharyngeal reflux (HRE) events in diagnosing laryngopharyngeal reflux (LPR) using ambulatory reflux monitoring. Data Sources PubMed, Cochrane Library, and Scopus. Review Methods A literature search was conducted about the normative data for PRE and HRE on multichannel intraluminal impedance–pH monitoring (MII-pH), hypopharyngeal-esophageal MII-pH (HEMII-pH), or oropharyngeal pH monitoring using PICOTS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…LPR was nonacid or weakly acid in more than half patients, and they had only upright and daytime HREs in 59% of cases [ 22 ]. The findings of this study corroborated those summarized in the systematic review of the Young Otolaryngologists of the International Federation of Otorhinolaryngological Societies [ 37 ]. The occurrence of daytime, upright, and gaseous HREs involved esophageal dysmotility, especially transient relaxations of the lower and upper esophageal sphincters.…”
Section: Diagnosis Of Reflux and Place Of Ph Studysupporting
confidence: 88%
See 4 more Smart Citations
“…LPR was nonacid or weakly acid in more than half patients, and they had only upright and daytime HREs in 59% of cases [ 22 ]. The findings of this study corroborated those summarized in the systematic review of the Young Otolaryngologists of the International Federation of Otorhinolaryngological Societies [ 37 ]. The occurrence of daytime, upright, and gaseous HREs involved esophageal dysmotility, especially transient relaxations of the lower and upper esophageal sphincters.…”
Section: Diagnosis Of Reflux and Place Of Ph Studysupporting
confidence: 88%
“…Interestingly, Harrel et al observed that adding a hypopharyngeal pH sensor in pH study increased the detection of abnormal pH values and supported the diagnosis of LPR more often than traditional dual-sensor esophageal monitoring [ 34 ]. Nowadays, the accuracy of single, dual-, or triple-probe pH-study devices is called into question regarding the lack of correlation between distal/proximal esophageal events and HREs and the lack of consideration of weakly acid or nonacid HREs [ 20 , 21 , 22 , 37 ].…”
Section: Diagnosis Of Reflux and Place Of Ph Studymentioning
confidence: 99%
See 3 more Smart Citations